Legitimando a cartilha da puérpera - PAIVA, Bruna Regina Pinheiro de (2019)
The postpartum period is defined as the period of pregnancy and childbirth in which the changes in the woman's body caused by pregnancy and childbirth return to pre-pregnancy status situation. Therefore, there are many doubts about this period and to try to help the mothers was created and applied a light technology. As health education tool used to Primer on Postpartum as it is a handy tool for the teaching and learning of mothers, characterized as important and viable alternative to help them during this period. The main objective is to legitimize the Primer on Postpartum. The work was carried out in three steps: first registered to primer for intellectual property registration, after the booklet was sent for two expertises and finally applied the primer and forms the target audience in order to know the mothers the booklet really helps in doubt issues that may arise in the puerperal period. And the last step was carried out in Guama the Municipal Health Unit of the city of Belém - Pará, 36 postpartum women. The present study had a quantitative approach and was developed as a health education proposal. Health education is strong ally in order to arouse behavior changes. Through it, the mothers were able to acquire information, reflect on their practices as well as on care in the postpartum period. Therefore among the methodological strategies we used the conversation wheel that is a feature that enables a greater exchange of information, enabling smooth speeches and various negotiations between researchers and participants. Data collection took place from May to July 2015. Data were collected using two forms, an applied before knowing the playbook and the other applied after contact with the instrument. The data collected had their variables distributed in spreadsheets Microsoft Office Excel 2010 program Analyzing the results, the discussion with the findings in the literature comparing them with the data that was collected was made. Most of the interviewed mothers were aged between 18 and 22 years (39%), married (45%) had a family income 1-2 times the minimum wage (47%) and were between one to two children (69%). According to the surveyed, 100% had doubts about questions of puerperal period and after contact with the primer 100% report that the instrument helped take the relevant questions. The results showed that most participants have learned the main issues surrounding the postpartum period, highlighting issues such as physical and psychological changes, breastfeeding, among other essential knowledge to postpartum women. The guidance given to mothers had positive effects, helping these women during this phase that difficult. So we can conclude by saying that the goal was reached, it was possible to perform the three steps and now the primer is validated and it is considered that the playbook of postpartum contribute by facilitating the process of teaching and learning among postpartum women, with regard guidance on the puerperal period.